Method for preparing carbon sequestration underground cemented filling material by carbonizing and activating all solid wastes and application of carbon sequestration underground cemented filling material

Through carbonization and activation of all solid waste technology, vaterite-type calcium carbonate precursors are prepared, which solves the problems of high energy consumption and carbon dioxide emissions caused by cement production, realizes the efficient utilization of industrial solid waste and the storage of carbon dioxide, and provides a low-cost, low-carbon underground filling material.

CN119569402AActive Publication Date: 2025-03-07HUBEI UNIV OF TECH

Patent Information

Application Number
CN202411661634.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-03-07
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

In the existing mine filling technology, the high energy consumption and large amount of carbon dioxide emissions caused by cement production have had a significant impact on the environment, and it has failed to effectively utilize industrial solid waste, especially alkaline industrial solid waste, to achieve carbon sequestration and low-carbon filling.

Method used

Through carbonization activation of all solid waste technology, vaterite-type calcium carbonate precursors are prepared, and combined with the synergistic action of inducers and stabilizers, carbon sealed underground cemented filling materials with high carbon sequestration, good water resistance and high strength are prepared.

Benefits of technology

It realizes the safe storage of carbon dioxide and the efficient utilization of industrial solid waste, reduces the carbon emissions of mine filling, and provides a low-cost, low-carbon underground filling material, meeting the performance requirements of mine filling and underground filling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569402A_ABST
    Figure CN119569402A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing a carbon sequestration underground cemented filling material by carbonizing and activating all solid wastes. Firstly, alkaline solid waste and water are compounded to obtain solid waste slurry, and an inducer and the solid waste slurry are stirred at a low speed to obtain first slurry; secondly, under the condition of continuously introducing carbon dioxide, carrying out wet grinding treatment on the first slurry to obtain second slurry, and then adding a stabilizer to continuously carry out wet grinding treatment to obtain third slurry; and finally, uniformly mixing the third slurry, semi-hydrated phosphogypsum, iron tailings and water, and vibrating for multiple times to obtain the carbon sequestration underground cemented filling material. The carbon sequestration rate of the prepared carbon sequestration underground cemented filling material can reach 12.2%-20.4%, the softening coefficient can reach 0.86, and the carbon sequestration underground cemented filling material meets the requirements of tailing concrete of C3 strength grade, F3 expansion degree and S1 shrinkage rate in JC / T 2478-2018 Mine Goaf Filling Tailing Concrete, and has a wide application prospect as a mine and underground filling material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of carbon sequestration, solid waste utilization and underground filling material preparation, and specifically to a method for preparing a carbon sequestration underground cementitious filling material by carbonizing and activating all solid waste, and also to the application of the above-mentioned carbon sequestration underground cementitious filling material in mines and underground filling. Background Art

[0002] Mine filling technology is an effective means to stabilize underground space and protect the environment. Traditionally, cement has been widely used as a filling material due to its excellent bonding properties and bearing capacity. However, with the increasing global attention to high-quality, low-carbon and green development, the concept of sustainable development in the construction industry has become an international consensus. As we all know, cement production is an energy-intensive process that consumes a lot of fuel to generate the high temperatures required for calcining and decomposing limestone. In addition, the use of fuel and the decarbonization of carbonates will lead to a large amount of carbon dioxide emissions, which will have a significant impact on the global greenhouse effect and climate change. According to statistics, carbon dioxide emissions from the cement industry account for about 8%-10% of the total global carbon dioxide emissions. Therefore, from the perspective of engineering cost and environmental protection, it is particularly urgent to further optimize and improve the cement-based filling technology in mines.

[0003] In the process of exploring low-carbon and low-cost underground filling materials, industrial solid wastes such as steel slag, slag, gypsum, carbide slag, red mud, etc. have shown great application potential. The use of these materials can not only reduce dependence on natural resources, but also effectively reduce carbon emissions. In particular, a large amount of alkaline industrial solid waste can achieve safe storage of carbon dioxide through wet carbon sequestration technology. The wet carbon sequestration process involves using alkaline industrial solid waste as raw materials, dissolving carbon dioxide in water to form carbonic acid, and then converting it into carbonate precipitation under alkaline conditions, thereby achieving long-term storage of carbon dioxide. This process not only promotes the resource utilization of solid waste, but also provides a safe and effective solution for carbon dioxide emission reduction.

[0004] CN111995275A discloses a fully solid waste underground filling material, which promotes the formation of cementitious materials through the synergistic stimulation of multiple solid wastes, thereby saving mine filling costs; CN112429986A discloses a fully solid waste underground filling cementitious material for high-sulfur tailings and its preparation method, and its performance is better than ordinary Portland cement; CN112279605A discloses an underground filling cementitious material and its preparation method and application, which improves the utilization rate of solid waste and reduces the preparation cost by alkali-stimulating all solid waste. CN112430022A discloses a fully solid waste foamed underground filling cementitious material for ultra-fine tailings and its preparation method, which uses chemical foaming technology to solve the requirements for low fineness and low cost of cementitious materials. In the above patents, the focus is mainly on saving mine filling costs and the utilization rate of solid waste, and no attention is paid to carbon emissions and the value-added utilization of carbonized products.

[0005] Based on this, developing an underground filling material with low carbon emissions and good filling performance is of great significance for carbon storage and utilization, as well as the promotion and application of solid carbon materials, and is also a technical problem that needs to be solved urgently. Summary of the invention

[0006] One of the purposes of the present invention is to provide a method for preparing underground cementitious filling materials for carbon sequestration by carbonizing and activating all-solid waste.

[0007] The second object of the present invention is to provide a carbon storage underground cementitious filling material with high carbon fixation rate, good water resistance, high strength grade and good filling performance.

[0008] The third object of the present invention is to provide a method for preparing a carbon-sealed underground cementitious filling material by carbonizing and activating all-solid waste and applying the material in mine filling and / or underground filling.

[0009] The technical solution adopted by the present invention to achieve one of the purposes is: to provide a method for preparing underground cementing filling materials for carbon sequestration by carbonizing and activating all solid waste, comprising the following steps: S1. Prepare a solid waste slurry with a solid content of 40%-60%; add an inducer to the solid waste slurry in an amount of 1.5wt.%-3.5wt.%, and then place it under a stirring speed of 10-30r / min for wet grinding for 30-60s to obtain a first slurry; the inducer is selected from a combination of one or more of ammonium citrate, glycine, ammonia water, triethylamine, alkanolamide, ammonium bicarbonate, and a mixture of NH4Cl and Na2SO4; S2. Add grinding media to the first slurry while continuously introducing CO2, and stir at a speed of 200-400 r / min for 15-20 min to obtain a second slurry; S3, continue to introduce CO2, and add a stabilizer to the second slurry in an amount of 1wt.%-2.2wt.%, and continue stirring at a speed of 400-600r / min for 10-20min to obtain a third slurry; the stabilizer is selected from a combination of one or more of sodium polystyrene sulfonate, sodium lauryl sulfate, polyvinyl pyrrolidone, polyethyleneimine, sodium tripolyphosphate or polyacrylamide; S4. Mix the third slurry, hemihydrate phosphogypsum, iron tailings and water in a certain proportion, and vibrate several times to obtain a carbon sequestration underground cementitious filling material.

[0010] The general idea of ​​the present invention is as follows: For underground filling materials, the filling performance in the initial stage of construction and the strength and shrinkage rate in the later stage of filling are important evaluation indicators. Based on the above considerations, the present invention proposes to introduce a large amount of vaterite calcium carbonate precursors in the preparation process of carbon sequestration underground cementitious filling materials, so as to improve the application performance of underground filling materials. Studies have found that vaterite calcium carbonate has a spherical structure and high activity, which not only significantly improves the continuity and fluidity of the filling material, but also helps to improve its later strength and reduce the shrinkage rate. In order to prepare a high proportion of vaterite calcium carbonate precursors in the slurry, the preparation method of the present invention mainly involves the following two improvements: On the one hand, the nucleation process of vaterite calcium carbonate is promoted. In step S1 of the present invention, the solid waste slurry is treated by the coordinated wet grinding carbonization activation technology, and an inducer in a suitable proportion is added. The inducer can increase the solubility of CO2 to obtain a higher CO3 2- / Ca 2+ ratio and system supersaturation to improve the carbon fixation efficiency; on the other hand, the calcium carbonate deposition nuclei produced after adding the inducer have sufficient surface free energy to promote the nucleation of vaterite calcium carbonate.

[0011] On the other hand, the stability of vaterite calcium carbonate is improved. In the operation of steps S2 and S3, the solid waste slurry generates calcium aluminate with higher permeability under the action of continuous mechanical force, which not only promotes the generation of calcium carbonate, but also stabilizes the dispersion of calcium carbonate with the steric effect produced by the subsequent addition of a suitable proportion of stabilizer, thereby promoting the in-situ formation of vaterite calcium carbonate. Further, this steric hindrance effect also suppresses the transformation of vaterite to calcite, stabilizes the vaterite crystal form generated in large quantities, and becomes the precursor material of carbon sequestration underground filling material.

[0012] In addition, the raw materials slag, steel slag, iron tailings, hemihydrate phosphogypsum, etc. used in the carbon sequestration underground cementitious filling material provided by the present invention are all industrial solid wastes. The present invention utilizes industrial solid wastes to treat the greenhouse gas CO2 and achieves the environmental protection goal of "treating waste with waste".

[0013] Further, in step S1, the inducing agent can form a stable complex with calcium ions, thereby affecting the nucleation and growth process of calcium carbonate. It has been found that when the inducing agent content is low, it is impossible to effectively complex enough calcium ions, resulting in an excessively high calcium ion concentration, which is unfavorable for the control of the calcium carbonate crystal form, thereby rapidly precipitating to form larger particles of calcite, affecting the fineness and dispersibility of the product, and then affecting the application performance of the product; and when the inducing agent dosage is too high, it will cause an imbalance in the ion concentration in the system, inhibit the process of calcium carbonate nucleation, reduce the precipitation efficiency of the product, and form more non-crystalline phases or impurities. Taking the above factors into consideration, the present invention adds an inducing agent to the solid waste slurry according to an addition amount of 1.5wt.%-3.5wt.%. Under this condition, a sufficient amount of inducing agent can form an effective combination with calcium ions, regulate the crystal form of calcium carbonate, promote the uniform growth of vaterite calcium carbonate, and avoid the irregular growth of crystals leading to unstable product quality.

[0014] Further, in step S3, the addition of stabilizer can reduce the surface tension of solution, and the steric hindrance effect produced stabilizes the dispersion of calcium carbonate, thereby promotes the in-situ formation of vaterite type calcium carbonate. Meanwhile, this steric hindrance effect also suppresses the transformation of vaterite to calcite. It is found through research that when the stabilizer dosage is low, the solid waste slurry cannot be effectively dispersed, resulting in poor uniformity of the product, the sedimentation of particles in the reaction system, and reduced reaction efficiency; and when the dosage is too high, it is easy to cause overdispersion, and the system produces too much foam, affecting the growth of calcium carbonate particles, and also affecting the stability and application performance of the product. Taking the above factors into consideration, the present invention adds stabilizer in the second slurry according to the addition amount of 1wt.%-2.2wt.%, can effectively disperse the particles in the solid waste slurry, prevent reunion, thereby contribute to the uniform growth of vaterite type calcium carbonate.

[0015] Furthermore, in the present invention, in order to promote the formation and stabilization of vaterite-type calcium carbonate and ensure product performance, different stirring speeds and times are set at different reaction stages: Among them, in step S1, after adding the inducer, wet grinding is performed for 30-60s at a rotation speed of 10-30r / min, which can increase the specific surface area of ​​the reactant, thereby improving the efficiency of subsequent reactions and the uniformity of the material. Low-speed stirring ensures that the inducer fully reacts with the calcium and magnesium ions in the solid waste slurry, and avoids excessive shear force or long stirring time to damage the structure of the inducer, thereby affecting the subsequent crystal form regulation effect.

[0016] In step S2, the rotating speed of 200-400r / min is stirred for 15-20min, and medium speed and continuous feeding of carbon dioxide are in order to efficiently be converted into carbonate ion under alkaline conditions by CO2, and then generate calcium carbonate with calcium ion reaction. Medium speed helps to maintain the uniformity of reaction system and the effective collision between reactants, promotes nucleation and growth of vaterite type calcium carbonate. If the speed setting is too high in this stage, the excessive fragmentation of particles in the reaction system may be caused, affecting crystal formation and stability of vaterite type calcium carbonate.

[0017] In step S3, after adding stabilizer, stir 10-20min at the rotating speed of 400-600r / min, adopt high-speed stirring to coordinate the adding of stabilizer and can stabilize the crystal formation of vaterite type calcium carbonate better.High-speed stirring helps dispersed and adsorption of stabilizer, and thermodynamic control is transformed into dynamics leading, and the vaterite type calcium carbonate of preferential deposition makes it be transformed into dynamics leading by thermodynamic control, and guarantees the uniform formation and stable of vaterite type calcium carbonate.This stage is too low as rotating speed, is unfavorable for dispersed of stabilizer, and if mixing speed is too high, can cause excessive agglomeration or destruction of calcium carbonate particles, affects the final performance of material.

[0018] Furthermore, in step S1, the solid waste slurry is formed by mixing alkaline solid waste and water in a mass ratio of 1:1; the alkaline solid waste includes slag and at least one of steel slag, carbide slag, and yellow phosphorus slag. Based on previous experiments and theoretical analysis, when the solid content in the solid waste slurry is 50%, the stability and reaction efficiency of the solid waste slurry can be significantly improved, and it is beneficial to balance the two performance indicators of the total carbon sequestration and compressive strength of the underground filling material.

[0019] Preferably, the solid waste slurry is made of steel slag, slag and water in a mass ratio of 1:1:2; the median particle size of steel slag and slag is ≤5mm, the slag activity index is ≥95%, and the steel slag alkalinity coefficient is ≥2.5. Among them, slag is beneficial to improve the cementing performance and durability of the filling material due to its highly active calcium silicate component. Compared with other alkaline solid wastes, using steel slag as a raw material for solid waste slurry has the following advantages: first, steel slag is one of the major solid wastes with huge domestic output and low utilization rate; second, steel slag contains a high content of free calcium oxide and magnesium oxide when it leaves the factory. If these components are directly used in the construction industry, they may cause concrete expansion, thereby reducing its stability and durability; third, the key reason why steel slag is difficult to utilize is that in addition to free calcium oxide and magnesium oxide, there is also the RO glass phase, which has potential hydration activity but is difficult to stimulate. The carbonization activation treatment of the present invention can effectively solve the above problems and achieve the overall goal of "waste treatment".

[0020] Furthermore, the steel slag and slag are obtained by crushing and screening; the steel slag contains a large amount of free calcium oxide and magnesium oxide. In the wet grinding and carbonization process of steps S1 and S2 of the present invention, the free calcium oxide and magnesium oxide in the steel slag are converted into calcium carbonate and magnesium carbonate by reacting with carbon dioxide. The synergistic effect of mechanical force and inducer promotes the decomposition of the RO phase glass in the steel slag; at the same time, the glass in the slag also undergoes a depolymerization reaction, breaking Si-O, Al-O and Ca-O bonds, thereby releasing silicate and aluminate ions. In high CO3 2− / Ca 2+ Under the condition of ratio, CO3 in the system 2− Supersaturation induces the nucleation of vaterite-type calcium carbonate.

[0021] Preferably, in step S1, the inducer is ammonium citrate, and the amount of ammonium citrate added to the solid waste slurry is 1.76wt.%-3.33wt.%; in step S3, the stabilizer is sodium polystyrene sulfonate, and the amount of sodium polystyrene sulfonate added to the second slurry is 1.18 wt.%-2 wt.%. Compared with other combinations of inducers and stabilizers, the combination of ammonium citrate + sodium polystyrene sulfonate can better improve carbon fixation efficiency, promote nucleation and stabilization of vaterite calcium carbonate, enhance the mechanical properties and filling properties of materials, achieve the environmentally friendly goal of "waste treatment", reduce production costs and improve the water resistance of materials. These comprehensive advantages make this combination significantly competitive in improving the performance of filling materials and environmental sustainability.

[0022] Furthermore, in step S2, zirconium oxide grinding balls are used as grinding media, and the grinding ball grading is 8 mm: 5 mm: 2.5 mm = 2: 3: 1. This ratio is designed according to wet grinding efficiency and energy distribution, which is beneficial to the fineness and uniformity of the material and improves the final performance of the product.

[0023] Furthermore, in step S2, the ball-to-material ratio is controlled to be (0.4-0.6):1. This ratio is designed based on the balance between wet grinding efficiency and cost control. A too small ratio may lead to low grinding efficiency, while a too large ratio may absorb too much water and lead to a decrease in efficiency. Preferably, the ball-to-material ratio is controlled to be 0.5:1.

[0024] In step S2, the addition of grinding media can increase the internal energy of the particles. On the one hand, it promotes the decomposition of the glass phase in steel slag and slag, releases silicate and aluminate ions, and provides more active sites for the formation of calcium carbonate. On the other hand, the effective collision of the addition of grinding media can strip the inert carbonization products attached to the surface of the reactants, thereby improving the carbonization efficiency and refining the calcium carbonate particle size.

[0025] Furthermore, in step S2, CO2 comes from tail gas emitted by industrial enterprises; the inlet flow rate of CO2 is 1-5L / min.

[0026] In steps S2 and S3 of the present invention, a process of efficient wet activated carbonization and synergistic mechanical force is adopted: in the wet activated carbonization process, the synergistic mechanical force treatment can promote the decomposition of the RO phase glass in the steel slag and the depolymerization of the glass in the slag. In the water environment, the high-speed collision of the steel slag and the slag with the grinding balls increases the internal energy of the particles, resulting in rapid activation of the alkali metal ions bonded to the surface. This causes the weaker non-covalent bonds to break, thereby dissolving the alkali metal ions. As the inert surface is continuously peeled off, the dissolution rate of the internal alkali metal ions is accelerated, effectively increasing the dissolution rate of the alkaline ions inside the steel slag and the total amount of carbon sequestration. The carbonation reaction forms highly active amorphous silica gel by removing calcium from the CSH interlayer and inducing CO3 in the system. 2− Supersaturation promotes the formation of vaterite calcium carbonate. Thermodynamic control changes to kinetic dominance, and the preferential deposition of vaterite calcium carbonate reflects the priority of kinetic control. In addition, the small-sized calcium carbonate particles produced by carbonation provide nucleation sites for the hydration of C3S and increase the density of the structural system.

[0027] Furthermore, the present invention obtains a third slurry with a median particle size of ≤40 μm based on the control of reaction conditions and parameters.

[0028] In some preferred embodiments, the median particle size of the third slurry is ≤4 μm. In the present invention, further reducing the median particle size of the third slurry can bring the following advantages: First, a median particle size of ≤4 μm can increase the specific surface area of ​​the particles, thereby improving the efficiency of the reaction with CO2, accelerating the nucleation and growth process of calcium carbonate and enhancing the activity of vaterite calcium carbonate; second, improving material properties: in cementitious filling materials, a median particle size of ≤4 μm helps to improve the uniformity and density of the material, thereby improving its mechanical properties and durability; third, ensuring the fluidity of the material: in the filling material, a median particle size of ≤4 μm distribution helps to maintain the fluidity of the material, which is convenient for construction and filling; fourth, controlling the pore structure of the material: a median particle size of ≤4 μm helps to form a more uniform and dense pore structure, thereby improving the strength and stability of the material.

[0029] Furthermore, in step S4, the mixing stirring speed is 30-60 r / min, the mixing time is 3-5 min, and the number of vibrations is 60-70 times.

[0030] The technical solution adopted by the present invention to achieve the second purpose is: to provide a carbon sequestration underground cementitious filling material, which is prepared by the method described in one of the purposes of the present invention; the composition of the carbon sequestration underground cementitious filling material includes, by weight: 150-170 parts of solid waste slurry, 15-20 parts of hemihydrate phosphogypsum, 420-630 parts of iron tailings, 73-93 parts of water, 3-5 parts of inducer, and 2-3 parts of stabilizer.

[0031] Furthermore, the median particle size of the hemihydrate phosphogypsum is ≤45μm, and the particle size of the iron tailings is 0.2-1.2mm. Among the above raw materials, the iron tailings have a huge output and a wide range of sources, and have very good compatibility with the products after wet grinding and carbonization; the sulfate component contained in the hemihydrate phosphogypsum reacts with the calcium carbonate generated during the carbonization process to form calcium sulfate, which plays a vital role in improving the strength and stability of the material. In addition, the introduction of hemihydrate phosphogypsum also injects new chemical activity into the system. The vaterite-type calcium carbonate and the iron tailings are cemented to not only act as crystal nuclei, providing abundant crystal nucleus sites to promote the growth of hydrated calcium silicate, but also form a continuous skeleton structure in the material, enhancing the cohesion of the material. This not only promotes the densification of the material, but also significantly improves the mechanical properties of the entire system.

[0032] Preferably, the inducer is ammonium citrate, which is an anhydrous powder with a content of ≥99%; the stabilizer is sodium polystyrene sulfonate, which is a light yellow transparent liquid with a solid content of 25%-35%. The use of sodium polystyrene sulfonate not only stabilizes the vaterite calcium carbonate, but also improves the pumpability and filling performance of the carbon sequestration underground filling material and reduces the sedimentation rate when added after 15-20 minutes of wet grinding and carbon fixation, replacing the use of water reducers and other ingredients in the preparation of conventional concrete materials.

[0033] The technical solution adopted by the present invention to achieve the third purpose is: to provide an application of the carbon sequestration underground cementitious filling material according to the second purpose of the present invention in mine filling and / or underground filling.

[0034] In some better embodiments, the carbon storage underground cementitious filling material has high water resistance and a softening coefficient greater than 0.86, which meets the requirements of C3 strength grade, F3 expansion and S1 shrinkage rate in tailings concrete for filling mine goafs; further, the carbon fixation rate of the carbon storage underground cementitious filling material reaches 12.2%-20.4%, realizing the storage and utilization of carbon dioxide and providing a new way for the high added value utilization of carbonization products.

[0035] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention provides a method for carbonizing and activating all solid waste to prepare underground cementing filling materials for carbon sequestration. During the wet grinding carbonization process, a certain proportion of inducer is added, and the synergistic effect of mechanical force and inducer is used to promote the decomposition of glass in the solid waste slurry to release silicate and aluminate ions. 2− / Ca 2+ Under the condition of ratio, CO3 in the system 2−Supersaturation induces the nucleation of vaterite calcium carbonate; in the subsequent wet grinding and carbon fixation process, a certain proportion of stabilizer is added. The steric hindrance effect of the stabilizer stabilizes the dispersion of calcium carbonate, promotes the in-situ formation of vaterite calcium carbonate, and inhibits the transformation of vaterite to calcite. The addition of inducers and stabilizers promotes the formation and stabilization of vaterite calcium carbonate. Vaterite calcium carbonate has a spherical structure and high activity, which not only significantly improves the continuity and fluidity of the filling material, but also helps to improve its later strength and reduce the shrinkage rate.

[0036] (2) The present invention provides a carbon sequestration underground cementing filling material, and the material used has good adaptability as an underground filling material. The introduction of hemihydrate phosphogypsum also injects new chemical activity into the system. The sulfate component contained in it reacts with the calcium carbonate generated during the carbonization process to form calcium sulfate, which plays a vital role in improving the strength and stability of the material. The output of iron tailings is huge and the source is wide, and it has very good adaptability with the product after wet grinding and carbonization. The vaterite-type calcium carbonate cemented with the iron tailings not only acts as a crystal nucleus and provides abundant crystal nucleus sites to promote the growth of hydrated calcium silicate, but also forms a continuous skeleton structure in the material, enhancing the cohesion of the material. This not only promotes the densification of the material, but also significantly improves the mechanical properties of the entire system.

[0037] (3) The carbon sequestration underground cementitious filling material prepared by the present invention has high water resistance and a softening coefficient greater than 0.86, meeting the requirements of C3 strength grade, F3 expansion and S1 shrinkage rate in JC / T 2478-2018 "Tailing sand concrete for filling mine goaf". In addition, the carbon fixation rate of the carbon sequestration underground cementitious filling material prepared by the present invention reaches 12.2-20.4%. While absorbing solid waste, it also realizes the sequestration and utilization of carbon dioxide, and provides a new way for the high added value utilization of carbonization products. It has broad promotion and application prospects as a mine or underground filling material. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 A schematic flow chart of a method for preparing underground cementitious filling materials for carbon sequestration by carbonizing and activating all-solid waste provided by the present invention. DETAILED DESCRIPTION

[0039] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0040] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.

[0041] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited thereto.

[0042] The chemical compositions of the main raw materials used in Examples 1-4 and Comparative Examples 1-3 of the present invention are shown in Table 1, wherein the iron tailings were obtained from an iron ore factory.

[0043] Table 1

[0044] The weight parts of the main raw materials and the experimental conditions in Examples 1-4 of the present invention and Comparative Examples 1-3 are shown in Table 2.

[0045] Table 2

[0046] In the above table, the mineral powder activity index is ≥95%; the inducer is ammonium citrate, which is an anhydrous powder with a content of ≥99%; the stabilizer is sodium polystyrene sulfonate, which is a light yellow transparent liquid with a solid content of 30%; the solid waste slurry is obtained by crushing and screening steel slag and slag (median particle size ≤5mm) and compounding with water in a mass ratio of 1:1:2; the carbon dioxide used in Examples 1-4 and Comparative Examples 1-3 is the industrial by-product gas source collected from industrial enterprises.

[0047] Example 1 A carbon storage underground cementing filling material, the raw material composition of which includes, by weight: 160 parts of solid waste slurry, 15 parts of hemihydrate phosphogypsum, 3 parts of ammonium citrate, 2 parts of sodium polystyrene sulfonate, 570 parts of iron tailings, and 93 parts of water. The preparation method of the carbon storage underground cementing filling material includes the following steps: Step 1: steel slag, slag and water are compounded (the mass ratio of steel slag: slag: water is 1:1:2) to obtain solid waste slurry, 3 parts of ammonium citrate and 160 parts of solid waste slurry are placed in a wet grinder, and stirred at 10 r / min for 60 seconds to obtain a first slurry; Step 2: CO2 was continuously introduced into the wet grinder at a flow rate of 1 L / min, and grinding balls (grinding ball gradation was 8 mm: 5 mm: 2.5 mm = 2: 3: 1, and the ball-to-material ratio was 0.5: 1) were added, and the first slurry was stirred at a speed of 300 r / min for 15 min to obtain a second slurry; Step 3: Continue to introduce CO2, add 2 parts of sodium polystyrene sulfonate to the second slurry, stir at a speed of 500 r / min for 10 minutes, and obtain a third slurry with a median particle size of ≤40 μm; wherein CO2 is continuously introduced in steps 2 and 3, the cumulative introduction time is 25 minutes, and the wet grinding environment is normal temperature and pressure; Step 4: Place the third slurry prepared in step 3, 15 parts of semi-hydrated phosphogypsum, 570 parts of semi-iron tailings and 93 parts of water in a mixer, mix them evenly at a speed of 30 r / min and vibrate them 60-70 times. The slurry mass concentration is 74%, and a carbon sequestration underground cementitious filling material is obtained.

[0048] Example 2 A carbon storage underground cementing filling material, the raw material composition of which includes, by weight: 170 parts of solid waste slurry, 20 parts of hemihydrate phosphogypsum, 5 parts of ammonium citrate, 3 parts of sodium polystyrene sulfonate, 630 parts of iron tailings, and 91 parts of water. The preparation method of the carbon storage underground cementing filling material includes the following steps: Step 1: steel slag, slag and water are compounded (the mass ratio of steel slag: slag: water is 1:1:2) to obtain solid waste slurry, 5 parts of ammonium citrate and 170 parts of solid waste slurry are placed in a wet grinder, and stirred at 20 r / min for 60 seconds to obtain a first slurry; Step 2: CO2 was continuously introduced into the wet grinder at a flow rate of 2 L / min, and grinding balls (grinding ball gradation was 8 mm: 5 mm: 2.5 mm = 2: 3: 1, and the ball-to-material ratio was 0.5: 1) were added, and the first slurry was stirred at a speed of 300 r / min for 20 min to obtain a second slurry; Step 3: Continue to introduce CO2, add 3 parts of sodium polystyrene sulfonate to the second slurry and stir at a speed of 500 r / min for 20 minutes to obtain a third slurry with a median particle size of ≤4 μm; wherein CO2 is continuously introduced in steps 2 and 3, the cumulative introduction time is 40 minutes, and the wet grinding environment is normal temperature and pressure; Step 4: Place the third slurry prepared in step 3, 20 parts of semi-hydrated phosphogypsum, 630 parts of semi-iron tailings and 91 parts of water in a mixer and mix them evenly at a speed of 30 r / min and vibrate 60-70 times. The slurry mass concentration is 76%, and a carbon sequestration underground cementitious filling material is obtained.

[0049] Example 3 A carbon storage underground cementing filling material, the raw material composition of which includes, by weight: 150 parts of solid waste slurry, 15 parts of hemihydrate phosphogypsum, 3 parts of ammonium citrate, 2 parts of sodium polystyrene sulfonate, 540 parts of iron tailings, and 89 parts of water. The preparation method of the carbon storage underground cementing filling material includes the following steps: Step 1: steel slag, slag and water are compounded (the mass ratio of steel slag: slag: water is 1:1:2) to obtain solid waste slurry, 3 parts of ammonium citrate and 150 parts of solid waste slurry are placed in a wet grinder, and stirred at 30 r / min for 30 seconds to obtain a first slurry; Step 2: CO2 was continuously introduced into the wet grinder at a flow rate of 5 L / min, and grinding balls (grinding ball gradation was 8 mm: 5 mm: 2.5 mm = 2: 3: 1, and the ball-to-material ratio was 0.5: 1) were added, and the first slurry was stirred at a speed of 400 r / min for 20 min to obtain a second slurry; Step 3: Continue to introduce CO2, add 2 parts of sodium polystyrene sulfonate to the second slurry and stir at a speed of 600 r / min for 20 minutes to obtain a third slurry with a median particle size of ≤10 μm; wherein the cumulative introduction time of CO2 in steps 2 and 3 is 25 minutes, and the wet grinding environment is normal temperature and pressure; Step 4: Place the third slurry prepared in step 3, 15 parts of semi-hydrated phosphogypsum, 540 parts of semi-iron tailings and 89 parts of water in a mixer and mix them evenly at a speed of 30 r / min and vibrate 60-70 times. The slurry mass concentration is 74%, and a carbon sequestration underground cementitious filling material is obtained.

[0050] Example 4 A carbon sequestration underground cementing filling material, the raw material composition of which includes, by weight: 170 parts of solid waste slurry, 20 parts of hemihydrate phosphogypsum, 3 parts of ammonium citrate, 3 parts of sodium polystyrene sulfonate, 420 parts of iron tailings, and 73 parts of water. The preparation method of the carbon sequestration underground cementing filling material includes the following steps: Step 1: steel slag, slag and water are compounded (the mass ratio of steel slag: slag: water is 1:1:2) to obtain solid waste slurry, 3 parts of ammonium citrate and 170 parts of solid waste slurry are placed in a wet grinder, and stirred at 20 r / min for 30 seconds to obtain a first slurry; Step 2: CO2 was continuously introduced into the wet grinder at a flow rate of 2 L / min, and grinding balls (grinding ball gradation was 8 mm: 5 mm: 2.5 mm = 2: 3: 1, and the ball-to-material ratio was 0.5: 1) were added, and the first slurry was stirred at a speed of 300 r / min for 15 min to obtain a second slurry; Step 3: Continue to introduce CO2, add 3 parts of sodium polystyrene sulfonate to the second slurry and stir at a speed of 400r / min for 10min to obtain a third slurry with a median particle size of ≤30μm; wherein, CO2 is first introduced continuously for 25min in steps 2 and 3; after step 3, CO2 is continued to be introduced for 15min without external stirring force, and the cumulative introduction time is 40min, and the wet grinding environment is normal temperature and pressure; Step 4: Place the third slurry prepared in step 3, 20 parts of hemihydrate phosphogypsum, 420 parts of iron tailings and 73 parts of water in a mixer, mix them evenly at a speed of 30 r / min and vibrate them 60-70 times. The slurry mass concentration is 72%, and a carbon sequestration underground cementitious filling material is obtained.

[0051] Comparative Example 1 The difference between this comparative example and Example 2 is that the wet grinding treatment time is shortened to 15 minutes. Specifically, the wet grinding treatment time of step 2 is adjusted to 10 minutes, and the wet grinding treatment time of step 3 is adjusted to 5 minutes. In steps 2 and 3, the CO2 flow rate is controlled to be 2L / min, and the CO2 is continuously introduced, and the cumulative introduction time is 15 minutes. The other operations remain unchanged, and a carbon sequestration underground cementing filling material is obtained.

[0052] Comparative Example 2 The difference between this comparative example and Example 2 is that: in step 3, CO2 introduction and stirring wet grinding treatment are continued, but sodium polystyrene sulfonate is not added as a stabilizer to stabilize the vaterite calcium carbonate, and the other operations remain unchanged to obtain a carbon sequestration underground cementitious filling material.

[0053] Comparative Example 3 The difference between this comparative example and Example 2 is that in step 1, ammonium citrate is not added as an inducer to regulate the formation of aragonite calcium carbonate, and the other operations remain unchanged to obtain a carbon sequestration underground cementing filling material.

[0054] Application performance testing The carbon sequestration underground cementitious filling materials prepared in Examples 1-4 and Comparative Examples 1-3 were tested for their application performance, wherein the carbon fixation rate was tested using the TG test method of GB / T 27761-2011 "Weight Loss by Thermogravimetric Analyzer"; the compressive strength was tested using the 28-day compressive strength test of JGJ / T70-2009 "Basic Performance Test Method for Building Mortar"; the 28-day shrinkage rate and expansion were tested using JC / T 2478-2018 "Tailing Sand Concrete for Mine Goaf Filling"; and the water resistance of the material was tested using the softening coefficient. The relevant test results are shown in Table 3.

[0055] Table 3

[0056] It can be seen from Table 3 above that The 28-day mortar compressive strength of the carbon sequestration underground cementitious filling materials prepared in Examples 1-4 of the present invention all exceeded 2.0 MPa, which complies with the requirements of C2 strength grade tailings concrete in the JC / T 2478-2018 standard "Tailings Concrete for Filling Mine Goafs"; the expansion of the carbon sequestration underground cementitious filling materials prepared in Examples 1-4 is greater than 350 mm, which complies with the F3 expansion grade requirement in the standard; the 28-day shrinkage rate of Examples 1-4 is also less than 6%, which complies with the S2 shrinkage rate grade requirement in the standard.

[0057] In particular, compared with Comparative Example 1 in which the wet grinding time is shortened to 15 min, the 28-day compressive strength of Example 2 is improved by 75.4%, the shrinkage rate is reduced by 119.4%, the expansion is increased by 48.9%, and the water resistance is improved by 26%; and compared with Comparative Example 2 in which the step of stabilizing vaterite calcium carbonate is not carried out, the 28-day compressive strength of Example 2 is improved by 111.1%, the shrinkage rate is reduced by 139.9%, the expansion is increased by 70.9%, and the water resistance is improved by 31%; compared with Comparative Example 3 in which the step of regulating vaterite calcium carbonate is not carried out, the 28-day compressive strength of Example 2 is improved by 91.1%, the shrinkage rate is reduced by 128.5%, the expansion is increased by 54.6%, and the water resistance is improved by 28%.

[0058] Furthermore, by comparing the experimental conditions and test results of Examples 1-4, it can be seen that the comprehensive performance of the underground cementitious filling material for carbon sequestration obtained in Example 2 is significantly better than that of other examples. On the one hand, in Example 2, the mass ratio of the inducer and the stabilizer is controlled to 5:3, which provides the optimal conditions for the nucleation of calcium carbonate and the maximization of the stability of vaterite-type calcium carbonate, and realizes the fine regulation of the nucleation and growth dynamics of the material; on the other hand, Example 2 obtains a slurry with a median particle size of ≤4μm by extending the wet grinding time and the synergistic action time of CO2 introduction, increasing the dosage of the inducer and stabilizer, and optimizing the experimental conditions. It not only has good fluidity, is convenient for construction and filling, and improves construction efficiency, but also improves the density and uniformity of the material, thereby further improving the mechanical properties, water resistance, stability and filling performance of the underground cementitious filling material for carbon sequestration.

[0059] In summary, the carbon fixation rate of the wet-ground steel slag and slag prepared by the synergistic carbonization and activation of the present invention for carbon sequestration of all-solid waste underground filling materials can reach 20.4% within 40 minutes. At the same time, the prepared carbon sequestration underground cementitious filling material can meet the requirements of C3 strength grade, F3 expansion and S1 shrinkage rate of tailings concrete, and has good application prospects for achieving carbon-free emission treatment of industrial solid waste, high added value utilization and the synergistic benefits of underground space.

[0060] The above are only preferred embodiments of the present invention, and are not intended to limit the implementation methods and protection scope of the present invention. Those skilled in the art should be aware that all solutions obtained by equivalent substitutions and obvious changes made using the contents of the specification of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing underground cementing filling materials for carbon sequestration by carbonizing and activating all solid waste, characterized in that: The following steps are involved: S1. Prepare a solid waste slurry with a solid content of 40%-60%; add an inducer to the solid waste slurry in an amount of 1.5wt.%-3.5wt.%, and then place it under a stirring speed of 10-30r / min for wet grinding for 30-60s to obtain a first slurry; the inducer is selected from a combination of one or more of ammonium citrate, glycine, ammonia water, triethylamine, alkanolamide, ammonium bicarbonate, and a mixture of NH4Cl and Na2SO4; S2. Add grinding media to the first slurry while continuously introducing CO2, and stir at a speed of 200-400 r / min for 15-20 min to obtain a second slurry; S3, continue to introduce CO2, and add a stabilizer to the second slurry in an amount of 1wt.%-2.2wt.%, and continue stirring at a speed of 400-600r / min for 10-20min to obtain a third slurry; the stabilizer is selected from a combination of one or more of sodium polystyrene sulfonate, sodium lauryl sulfate, polyvinyl pyrrolidone, polyethyleneimine, sodium tripolyphosphate, and polyacrylamide; S4. Mix the third slurry, hemihydrate phosphogypsum, iron tailings and water in a certain proportion, and vibrate several times to obtain a carbon sequestration underground cementitious filling material.

2. The method according to claim 1, characterized in that In step S1, the solid waste slurry is formed by mixing alkaline solid waste and water in a mass ratio of 1:1; the alkaline solid waste includes slag and at least one of steel slag, carbide slag and yellow phosphorus slag.

3. The method according to claim 1, characterized in that The inducer is ammonium citrate, and the amount of ammonium citrate added to the solid waste slurry is 1.76wt.%-3.33wt.%; the stabilizer is sodium polystyrene sulfonate, and the amount of sodium polystyrene sulfonate added to the second slurry is 1.18 wt.%-2 wt.%.

4. The method according to claim 1, characterized in that In step S2, the grinding medium is zirconia grinding balls, and the grinding ball gradation is 8mm:5mm:2.5mm=2:3:1; the ball-to-material ratio is (0.4-0.6):

1.

5. The method according to claim 1, characterized in that In step S2, CO2 comes from tail gas emitted by industrial enterprises; the inlet flow rate of CO2 is 1-5L / min.

6. The method according to claim 1, characterized in that In step S3, the median particle size of the third slurry is ≤40 μm.

7. The method according to claim 1, characterized in that In step S4, the stirring speed of the mixing is 30-60 r / min, the mixing time is 3-5 min, and the number of vibrations is 60-70 times.

8. A carbon sequestration underground cementing filling material, characterized in that: Prepared by the method according to any one of claims 1-7; The composition of the underground cementing filling material for carbon sequestration includes, by weight: 150-170 parts of solid waste slurry, 15-20 parts of hemihydrate phosphogypsum, 420-630 parts of iron tailings, 73-93 parts of water, 3-5 parts of inducer, and 2-3 parts of stabilizer.

9. The underground cementing filling material for carbon sequestration according to claim 8, characterized in that: The median particle size of the hemihydrate phosphogypsum is ≤45 μm, and the particle size of the iron tailings is 0.2-1.2 mm.

10. Use of the carbon sequestration underground cementitious filling material according to claim 8 or 9 in mine filling and / or underground filling.

Citation Information

Patent Citations

  • All-solid-waste underground filling cementing material and preparation method thereof

    CN111995275A

  • Underground filling cementing material as well as preparation method and application thereof

    CN112279605A

  • All-solid-waste underground filling cementing material for high-sulfur tailings and preparation method of all-solid-waste underground filling cementing material

    CN112429986A

  • All-solid-waste foamed underground filling cementing material for ultrafine tailings and preparation method of cementing material

    CN112430022A

  • Method for preparing regenerated cementing material by utilizing phosphogypsum synergistic carbon sequestration pretreatment process

    CN114956759A

Cited By

  • Vaterite type stable artificial aggregate prepared by synergistically using pomegranate rind and steel slag

    CN121362002A

  • Carbonized wet-ground steel slag-lithium slag-based composite admixture and application thereof

    CN121974575A